Coalition for the Poudre River Watershed - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2015)
Located in: Fort Collins office files. Coalition for Poudre River Watershed (CPRW) records related to Colorado State Forest Service (CSFS) State Fire Assistance (SFA) and Wildland Urban Interface (WUI). Includes: WUI competitive grant project award notification; grant applications; scope of work reports; program payment and reimbursement requests; cost documentation worksheets; financial statements; invoices; maps; correspondence to include printouts of emails; as well as Ben Delatour Scout Ranch Forest Restoration Collaborative treatment plan and prescription report.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado